2018
DOI: 10.1182/blood-2017-09-807024
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 inhibition exerts its antileukemic effect by recommissioning PU.1- and C/EBPα-dependent enhancers in AML

Abstract: Epigenetic regulators are recurrently mutated and aberrantly expressed in acute myeloid leukemia (AML). Targeted therapies designed to inhibit these chromatin-modifying enzymes, such as the histone demethylase lysine-specific demethylase 1 (LSD1) and the histone methyltransferase DOT1L, have been developed as novel treatment modalities for these often refractory diseases. A common feature of many of these targeted agents is their ability to induce myeloid differentiation, suggesting that multiple paths toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 39 publications
11
84
1
Order By: Relevance
“…Interestingly, LSD1 pharmacological inhibition phenocopied the knockdown effects in human patient AML cells and murine models, and it also prevented the establishment of the disease, upon murine MLL-AF9 AML cell transplantation into sub-lethally irradiated CD45.1 + congenic mice [84]. In line with these results, a recent work by Cusan et al showed that LSD1 inhibition induced global accessibility onto dynamic sites of chromatin and occupancy by the myeloid transcription factors PU.1 and C/EBPα in murine MLL-F9 cells, leading to premature developmental arrest at the stage of granulocyte-macrophage progenitor [85]. Both of these studies [84,85] underlined the fact that LSD1 attenuation released LSCs from this "premature" differentiation arrest and sensitized them to anti-cancer treatments with promising results.…”
Section: Lsd1 In Malignant Hematopoietic Stem Cellsmentioning
confidence: 68%
“…Interestingly, LSD1 pharmacological inhibition phenocopied the knockdown effects in human patient AML cells and murine models, and it also prevented the establishment of the disease, upon murine MLL-AF9 AML cell transplantation into sub-lethally irradiated CD45.1 + congenic mice [84]. In line with these results, a recent work by Cusan et al showed that LSD1 inhibition induced global accessibility onto dynamic sites of chromatin and occupancy by the myeloid transcription factors PU.1 and C/EBPα in murine MLL-F9 cells, leading to premature developmental arrest at the stage of granulocyte-macrophage progenitor [85]. Both of these studies [84,85] underlined the fact that LSD1 attenuation released LSCs from this "premature" differentiation arrest and sensitized them to anti-cancer treatments with promising results.…”
Section: Lsd1 In Malignant Hematopoietic Stem Cellsmentioning
confidence: 68%
“…[12][13][14] KDM1A is overexpressed in primary SCLC, 15 and its inhibition in acute myeloid leukemia (AML) has been shown to relieve the differentiation block, thereby exerting an antileukemic effect and sensitizing AML cells to anticancer therapy. 16,17 Furthermore, inhibition of KDM1A provided an antileukemic effect in secondary engraftment models, indicating an effect on the leukemiainitiating cell population and further suggesting a role for KDM1A in the self-renewal of cancer stem cells. 18 Both SCLC and AML are poorly differentiated tumors 19,20 ; thus, inhibition of KDM1A may invoke a similar differentiation mechanism in SCLC.…”
Section: Introductionmentioning
confidence: 91%
“…One well-characterized consequence of LSD1 inhibition is induction of myeloid maturation or differentiation, which is associated with cell surface upregulation of the type I transmembrane protein, CD86 11,37-40 . To determine if perturbation of the p53 pathway affects LSD1 inhibitor-mediated upregulation of cell surface CD86 expression, we treated GMP-MLL-AF9 cells expressing shRNAs targeting either p53 or Renilla with IMG-7289 and measured cell surface induction of CD86.…”
Section: Resultsmentioning
confidence: 99%